PENGARUH DIVIDEN PAYOUT RATIO, FINANCIAL LEVERAGE DAN PROFITABILITAS TERHADAP BETA SAHAM: (Studi Kasus Pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) Tahun 2011-2013) - Suci Ramadani; Sri Mulyati; Icih Icih (STIESA Press, 2019)
Jakarta Islamic Index is an index comprised of stocks that meet various criteria sharia. Islamic stocks beta is a measure of the risk of the shares belonging to sharia. This study aims to examine and determine the influence of fundamental factors to Islamic stock beta. Object of this research is the company that makes the Jakarta Islamic Index years 2011-2013, with purposive sampling technique gained 12 companies as the study sample. The independent variabel in this study is dividend payout ratio (DPR), financial leverage (FL) and profitability. This research using multiple regression analysis to test the hypotesis. Result showed that the variables dividen payout ratio has no effect on beta Islamic stock. Variable financial leverage and profitability variables significant positive effect on beta Islamic stock. Simultaneous dividen payout ratio, financial leverage and profitability significantly to the beta having an Islamic stock